ANTI-HEROISM IN THE CHARACTER OF LOGAN IN JAMES MANGOLD'S LOGAN (2017) - Dhafin Aditya Nugraha, - (Universitas Pendidikan Indonesia, 2023)
Antiheroism has been a popular subject in various works of literature since this type of character often reflects real-life people who are neither all good nor all bad. This study aims to discover what antiheroism traits are reflected in the character of Logan in James Mangold's film Logan (2017). The data uses a qualitative method and textual analysis in the form of screenshots of the film and dialogue scripts. This study used the theory of characterization in films by Boggs and Petrie (2004), which mainly focuses on the appearance, dialogue, and actions; and the combined theory of antihero traits proposed by Wilson et al. (2013), Brombert (1999), and Al-Jubouri (2022). The result of this study shows that throughout the film, Logan has mostly shown four antihero traits: being weak, being unhappy, having empathy, and being selfish. From the analysis, it can be concluded that Logan can be considered an antihero. This study shows that some antiheroes not only have good traits, as heroes usually do, but also negative traits. The antihero traits of Logan can be said to represent a real-life person, neither all good nor all bad.